Visitor perception on the potential of matang mangrove forest reserve for ecotourism - Abdul Latif, Farah Liyana (2016)
In peninsular Malaysia, Matang mangrove forest reserve is the larger mangrove area which is about 40,711 hectares. Matang Mangrove Forest is a national treasure, it was lies under federal and state authorities. Since early 1904, Matang Mangrove Forest being forest reserve with systematic management. This study was conducted at Matang mangrove forest to identify the potential of Matang mangrove forest as an ecotourism destination. There were 137 questionnaire was distributed to the visitor during weekend and public holidays in the month of February 2016. This study finds that there are three significant factors that influence potential of Matang mangrove by visitor perception. The factor are satisfaction and need, relaxation and leisure and malaysian certificate of educational. The research finding gives an understanding on what people's needs and wants for their recreational activities where it is useful to the related agency for their future management purpose.